Objective Determination of Standard of Care: Use of Blind Readings by External Radiologists - Semelka, Richard C.; Ryan, Andrew F.; Yonkers, Shannon; Braga, Larissa (American journal of roentgenology (1976), 2010)
The purpose of this study was to determine whether specific findings determined to be critical and standard of care by expert witnesses in a legal case are identifiable by radiologists blinded to clinical outcome and litigation. Images from six CT studies were sent to radiologists for interpretation. Two studies were performed for screening after major trauma, one of the cases being the subject of a settled legal action; three were randomly selected from studies performed in the evaluation of emergency department patients; and one was the control. The cases were selected to simulate a typical emergency department caseload. In the medicolegal case, four plaintiff expert witness radiologists had identified three findings in the CT study that were not described by the radiologist of record (primary reader). One of these findings was considered critical and was the basis for the legal case. Thirty-one radiologists participated in the study. The three findings made by the expert witnesses-T3 and T10 vertebral body fractures and 1-mm symmetric widening of the facet joints at T10-were made by none, 19 (61.3%), and none of the 31 radiologists in this study. Thirty-one radiologists who had no knowledge of the clinical outcome or litigation did not confirm the expert witness interpretation. This finding prompts questions about the current method of determining standard of care in legal cases, that is, use of paid medical expert witnesses. Our findings suggest that use of radiologists blinded to clinical outcome may be a more objective method of evaluating legal cases.